Cenozoic Antarctic climate evolution based on molecular and isotopic biomarker reconstructions from geological archives in the Ross Sea region - Bella Duncan (2017)
During the Cenozoic Era (the last 65 Ma), Antarctica’s climate has evolved from ice free conditions of the ‘Greenhouse world’, which at its peak (~ 55 Ma) supported near-tropical forests, to the ‘Icehouse’ climate of today with permanent ice sheets, and a very sparse macroflora. This long-term cooling trend is punctuated by a number of major, abrupt, and in some cases, irreversible climate transitions. Reconstructing past changes in vegetation, sea surface temperature, hydroclimate and the carbon cycle require robust geological proxies that in turn can provide insights into climatic thresholds and feedbacks that drove major transitions in the evolution of Antarctica’s ice sheets. Biomarkers allow climate and environmental proxy reconstructions for this region, where other more traditional paleoclimate methods are less suitable. This study has two aims. Firstly to assess the suitability and applicability of biomarkers in Antarctic sediments across a range of depositional settings and ages, and secondly to apply biomarker-based climate proxies to reconstruct environmental and climate conditions during key periods in the development of the Antarctic Ice Sheets. The distribution and abundances of n-alkanes are assessed in Oligocene and Miocene sediments from a terrestrial outcrop locality in the Transantarctic Mountains, and two glaciomarine sediment cores and an ice-distal deep marine core from the western Ross Sea. Comparisons are made with n-alkane distributions in Eocene glacial erratics and sedimentary rocks of the Mesozoic Beacon Supergroup, both likely sources of reworked material. A shift in dominant chain length from n-C₂₉ to n-C₂₇ occurs between the Late Eocene and Early Oligocene, considered a response to a significant climate cooling. Samples from glaciofluvial environments onshore, and subglacial and ice-proximal environments offshore display a reworked n-alkane distribution, characterised by low carbon preference index (CPI), high average chain length (ACL) and high n-C₂₉/n-C₂₇ values. Whereas, samples ...